2016
DOI: 10.1016/j.jacc.2016.03.605
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Sarcoidosis

Abstract: Clinically manifest cardiac involvement occurs in perhaps 5% of patients with sarcoidosis. The 3 principal manifestations of cardiac sarcoidosis (CS) are conduction abnormalities, ventricular arrhythmias, and heart failure. An estimated 20% to 25% of patients with pulmonary/systemic sarcoidosis have asymptomatic cardiac involvement (clinically silent disease). In 2014, the first international guideline for the diagnosis and management of CS was published. In patients with clinically manifest CS, the extent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
438
1
36

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(478 citation statements)
references
References 65 publications
3
438
1
36
Order By: Relevance
“…Cardiovascular manifestations were defined by the presence of the following disease classes in the primary or secondary diagnosis fields: conduction disorders, arrhythmias, heart failure, nonischemic cardiomyopathy, and pulmonary hypertension (Table S2). 18, 20, 21, 22 The NIS variables were used to identify demographic and baseline characteristics of sarcoidosis hospitalizations. Comorbidities used in our study were derived from Elixhauser method for quantification of comorbidities 14.…”
Section: Methodsmentioning
confidence: 99%
“…Cardiovascular manifestations were defined by the presence of the following disease classes in the primary or secondary diagnosis fields: conduction disorders, arrhythmias, heart failure, nonischemic cardiomyopathy, and pulmonary hypertension (Table S2). 18, 20, 21, 22 The NIS variables were used to identify demographic and baseline characteristics of sarcoidosis hospitalizations. Comorbidities used in our study were derived from Elixhauser method for quantification of comorbidities 14.…”
Section: Methodsmentioning
confidence: 99%
“…Cardiac involvement is clinically manifest in just 5% to 10% of sarcoidosis patients, but can be identified at autopsy in approximately 25% and is the most frequent cause of death (1,2). The accurate diagnosis of subclinical but active cardiac sarcoidosis (aCS) is, therefore, important (1); however, a gold standard assessment remains lacking.…”
mentioning
confidence: 99%
“…Cardiac involvement is clinically manifest in just 5% to 10% of sarcoidosis patients, but can be identified at autopsy in approximately 25% and is the most frequent cause of death (1,2). The accurate diagnosis of subclinical but active cardiac sarcoidosis (aCS) is, therefore, important (1); however, a gold standard assessment remains lacking. The yield of endomyocardial biopsy is low due to the patchy distribution of myocardial disease (3), the Japanese Ministry of Health and Welfare criteria (4) lack sensitivity, and echocardiographic findings of regional wall thickening/thinning or motion abnormalities are neither specific nor sensitive (1).…”
mentioning
confidence: 99%
“…40% already had an implantable cardiac defibrillator prior to PET/CT, mean ejection fraction was 47 ± 16%, and JMHWG criteria turned positive in 34% of study population. In this line of thought, a recent review that included eight studies on prevalence and prognosis of clinically silent CS reported a more favourable course in clinical silent CS in five out of these eight studies: within a mean follow‐up of 23 months, no adverse cardiac event like ventricular arrhythmia or death was reported 24. It illustrates that differences in cardiac symptomatology of study population may influence adverse events' occurrence.…”
Section: Discussionmentioning
confidence: 98%